Optimizing legume seed production potential in the tropics: strategies for improving the distribution and replication of sustainable livestock - Sotelo, Mauricio E. (CGIAR Initiative on Sustainable Animal Productivity, 2023)
One of the great challenges facing the agricultural sector worldwide is the availability of fertile land for the establishment of crops for human and animal feed. Grass pastures used for animal feed, particularly cattle, are one of the crops with the highest land use, not only in LAC but also worldwide. However, poor practices and inadequate management of natural resources have led to a decrease or loss of soil nutrients, which leads to soil degradation. According to Gardi et.al., (2014) it is estimated that about 14% of degraded soils in the world are in Latin America and the Caribbean (LAC), so one of the current challenges is to recover the fertility of these so that the expansion of the agricultural frontier is gradually reduced.